Waveguide-Based Antenna Arrays for 5G Networks - Arismar Cerqueira Sodré; Igor Feliciano da Costa; Renan Alves dos Santos; Hugo Rodrigues Dias Filgueiras; Danilo Henrique Spadoti (International Journal of Antennas and Propagation)
This work reports the development of two high-performance waveguide-based antenna arrays for 5G cellular networks, operating in the underutilized millimetre wave (mm-wave) frequency spectrum. Two different scenarios of mm-wave communications are proposed for illustrating the applicability of the proposed arrays, which provide specific radiation patterns, namely, 12 dBi gain omnidirectional coverage in the 28 GHz band and dual-band sectorial coverage using the 28 and 38 GHz bands with gain up to 15.6 dBi. Numerical and experimental results of the array reflection coefficient, radiation pattern, and gain have been shown in an excellent agreement.